Effect of bucket hydrotherapy on clinical parameters in infants with bronchopulmonary dysplasia: A pilot randomized clinical trial - Vanessa S Probst; Darllyana S Soares; Victoria C Escobar; Marcia L.C. Camargo; Walter Sepulveda- Loyola; Josiane M Felcar; Lígia S. L. Ferrari (Canadian Journal of Respiratory Therapy)
# Introduction